Hesperoides, a new “hairy” flea beetle genus from southern Africa (Coleoptera: Chrysomelidae, Galerucinae, Alticini) - Maurizio Biondi (Fragmenta entomologica, 2017)
Hesperoides afromeridionalis gen. nov. and sp. nov. from the Republic of South Africa (Western and Eastern Cape Provinces and KwaZulu-Natal) is described. Despite some similarities with Hespera Weise, it exhibits major affinities with the genera attributed to the subtribe Aphthonini, especially with Aphthona Chevrolat and Montiaphthona Scherer. Data on distribution are supplied, along with preliminary ecological notes. Photomicrographs of main morphological characters, including male and female genitalia, and metafemoral extensor tendon are provided. Key to the six “hairy” flea beetle genera occurring in sub-Saharan African and their habitus photos are also given.